103 ORTHOGERIATRIC SERVICES IN THE FACE OF COVID-19. (18th November 2021) - Davey, N; McFeely, A; Doyle, P; Stankard, A; Coveney, S; Alsubie, N; O'Connor, J; Conlon, B; Monahan, P; Byrne, P; Britton, D; Halpin, T; et al.
Abstract: Background: Nationally agreed standards improve the level of care delivered to all older, frail, multi-morbid patients presenting with hip fractures. Dedicated Orthogeriatric services allow for these standards to be achieved in a multi-disciplinary team (MDT) setting. As the COVID-19 pandemic reached our shores, the model of care set out by the Irish Hip Fracture Standards (IHFS) was under threat. Our dedicated Orthopaedic Trauma ward became an acute COVID ward and the Orthogeriatric service was re-deployed to acute medicine for Quarter 2. Methods: Using the Irish Hip Fracture Database, local data was analysed and compared with national data from Quarter 1 to 4 (Q1–4) in 2020. Results: When comparing local IHFS's with national figures, ongoing challenges and future goals are highlighted. In 2020, there were 222 hip fracture patients (mean age 81.8 years) in our hospital. Standard 1, time to the ward <4 hours, stands at 71% locally (national average 33%). Standard 2, time to theatre <48 hours, is an ongoing challenge and remains at 66% (national average 75%). Standard 3, pressure ulcer rate, was the same as the national average at 3%. Standards 4, 5 and 6 in our hospital stand at 87% (national averages of 82%, 91% and 85% respectively). In Q1, 56%, or over 1 in every 2 patients with hip fractures, met all of the Irish Hip Fracture Standards in our hospital. In Q2, only 18% of patients met all of the IHFS's. Q3 saw improvements with 47% of all hip fracture patients achieving all IHFS's. Q4 showed maintenance with 45% of all patients achieving all IHFS's. Conclusion: These findings highlight the need for a dedicated Orthogeriatric Service and Orthopaedic ward at all times. Going forward with the risk of future waves and the emergence of new variants, every effort should be made to maintain a comprehensive orthogeriatric service to minimise a negative impact on patient care.